INOVAÇÃO EM TEMPOS DE PANDEMIA: ADAPTAÇÕES E DESAFIOS DO PROJETO DE EXTENSÃO PUC MAIS IDADE BETIM - Amorim, Maria Clara B. V.; Cruz, Agatha C. F.; Silva, Dayane J. R.; Carmos, Mariana P. D. S.; Martins, Nayara G.; Balbi, Sabrina Oliveira Viana (Sinapse Múltipla, 2020)